Optimization of Drying Process for Production Red Ginger Granulated Palm Sugar Using Response Surface Methodology (Universitas Negeri Semarang, 2022)
Palm sugar is used as a natural sweetener that is added to food and beverages. The nutritional content in palm sugar can be enriched with the addition of antioxidants derived from red ginger (Zingiber officinale var. rubrum). The antioxidant activity of red ginger is 75.61% higher than that of emprit ginger and elephant ginger. The problem that arises during the production process of granulated palm sugar is the drying process that has not considered chemical characteristics, especially water content. The requirement for water content of palm sugar according to SNI 01-3743-1995 is a maximum of 3%. Moisture content is the main parameter that determines the quality of granulated palm sugar to long shelf life. Water content can affect other chemical characteristics such as sucrose, reducing sugar, ash content, calories, protein, fat, and carbohydrates. This optimization is using RSM (Response Surface Methodology) CCD model (Central Composite Design) on Software Statistica 10 with 20 treatments. The independent variables used were time (4-6 hours), material weight (100-300) grams, and material size (10-26 mesh). Data processing with Statistica 10 software resulted in the optimum water content condition of 2.9019%, with the drying process conditions covering 6.68 hours, material weight 368.18 grams, and material size 31.45 mesh. Validation was carried out to test the accuracy of the optimization results from Statistica 10 Software. The validation of the moisture content results obtained a value of 2.9016%, with an error percentage of 0.0003%. The chemical characteristic test was applied to the granulated palm sugar as a result of optimization so that the value of sucrose (96.5967%) was obtained, reducing sugar (6.0434%), ash content (1.8660%), calories (379.93%), protein (2,4268%), fat (0.3972%), and carbohydrates (91,5379%)